Isolation of an Acidic Surface Antigen from a Conventional Strain of Staphylococcus aureus - Karakawa, W. W. (1974)
Staphylococcus aureus strain 7007, a prototype isolated from a hospital burn unit, was shown to exhibit a significant degree of resistance to ingestion by mouse polymorphonuclear leukocytes. An acidic surface antigen was isolated from strain 7007 by a combination of 10% trichloroacetic acid extraction, ion-exchange chromatography, and gel filtration. Chemical analysis indicated that the surface antigen consists of an unknown aminouronic acid and an amino sugar. Immunochemical analysis suggested that the 7007 antigen is a common feature of all the strains collected from the burn unit. No cross-reactivity was observed between the carbohydrate preparations of various hospital staphylococcal strains and the 7007 heteropolymer. These results suggested the possibility that the surface antigen of strain 7007 represents a strain- or type-specific antigen.